Kinetics of development of spontaneous apoptosis in B cell hybridoma cultures - Vomastek, T; Franĕk, F (Immunology letters, 1993)
The kinetics of the development of apoptosis was studied in mouse B cell hybridoma batch cultures carried out in the iron-rich protein-free medium. One of the markers of apoptosis, the apoptotic index reflecting the relative number of bodies insoluble in 6 M guanidinium hydrochloride, was found to rise significantly at 144 h, i.e., in the late stationary phase. At the decline of the culture (216 h) the value of the apoptotic index reached 29.1%. Analysis of another marker, the degree of DNA fragmentation determined on the basis of chromatographic resolution of isolated cellular DNA, revealed a significant increase as early as 96 h, i.e., at the end of the exponential phase. At 216 h the net value of the fragmented DNA fraction was about 30% of cellular DNA. The values of both markers were found to be very similar when the iron-rich protein-free supplement was replaced with conventional 10% foetal calf serum. This finding suggested that the growth factors present in the serum were not able to abolish the tendency of the hybridoma culture to undergo spontaneous apoptosis. The timing of the spontaneous onset of apoptosis in the exponential phase indicated that B cell hybridoma apoptosis was a process associated with cell proliferation and full metabolic activity rather than with the decline of cell vitality.
Keywords: kinetika; myši; Culture Media; buněčné dělení; B-lymfocyty; Animals; Kinetics; apoptóza; zvířata; B-Lymphocytes; Cell Division; Mice; Hybridomas; DNA; hybridomy; Apoptosis; kultivační média